Analisis Kondisi Lingkungan Kerja dalam Meningkatkan Employee Engagement pada Karyawan Bagian Produksi Industri Manufaktur di Cimahi - Gunawan, Riki; Senen, Syamsul Hadi; Tarmedi, Eded (Journal of Business Management Education (JBME), 2019)
Employee engagement is one of the main issues in human resources management and organizations, because it is considered as a major factor in measuring the strength of a company. Issues regarding employee engagement occur in various industries, including manufacturing. It's like what happened to PT. Pola Manunggal Sejati Cimahi, low indicator of employee engagement can be seen from high employee turnover, increased absence, and production targets that have decreased every year, so that the resulting production especially in the year 2016-2018 did not achieve the targets set by the company. This research uses descriptive and verification method, with explanatory survey method. The sampling technique used is probability sampling using the simple random sampling which amounted to 81 people. Data analysis technique used is simple linear regression with program tools SPSS (Statistical Product for Service Solution) 25.0 for Windows. The results of this study indicate that the description of the work environment in good category, description of the employee engagement in high category, and the employee engagement is affected by the work environment. So that the work environment should be considered in support of improving employee engagement.